Prolonged administration of maraviroc reactivates latent HIV in vivo but it does not prevent antiretroviral-free viral rebound - María Rosa López-Huertas (Nature Portfolio, 2020)
Abstract Human immunodeficiency virus (HIV) remains incurable due to latent viral reservoirs established in non-activated CD4 T cells that cannot be eliminated via antiretroviral therapy. Current efforts to cure HIV are focused on identifying drugs that will induce viral gene expression in latently infected cells, commonly known as latency reversing agents (LRAs). Some drugs have been shown to reactivate latent HIV but do not cause a reduction in reservoir size. Therefore, finding new LRAs or new combinations or increasing the round of stimulations is needed to cure HIV. However, the effects of these drugs on viral rebound after prolonged treatment have not been evaluated. In a previous clinical trial, antiretroviral therapy intensification with maraviroc for 48 weeks caused an increase in residual viremia and episomal two LTR-DNA circles suggesting that maraviroc could reactivate latent HIV. We amended the initial clinical trial to explore additional virologic parameters in stored samples and to evaluate the time to viral rebound during analytical treatment interruption in three patients. Maraviroc induced an increase in cell-associated HIV RNA during the administration of the drug. However, there was a rapid rebound of viremia after antiretroviral therapy discontinuation. HIV-specific T cell response was slightly enhanced. These results show that maraviroc can reactivate latent HIV in vivo but further studies are required to efficiently reduce the reservoir size.